Virtual reality driving simulator for analysis of user response time - Karne, Rahul (Kansas State University, 2019)
The purpose of this master’s thesis is to investigate and analyze the ability of individual users of a virtual reality (VR) driving simulator to react to a set of complex scenarios involving various accident-prone scenarios in a mixed virtual environment. The virtual environment is realistic enough to examine the response times in complex scenarios, and to identify the response time taken and the factors affecting it. The final result identifies the response time and represented the correlation between demographics and the driver’s behavior.
Keywords: Virtual reality; Driving; Simulation